Overexpression of microRNA-203 Suppresses Proliferation, Invasion, and Migration while Accelerating Apoptosis of CSCC Cell Line SCL-1 - Wenyun Ting; Cheng Feng; Mingzi Zhang; Fei Long; Ming Bai (Elsevier, 2020)
Cutaneous squamous cell carcinoma (CSCC) is a malignant proliferation of cutaneous epithelium that has been observed to have an alarming rise in incidence. Numerous studies have demonstrated microRNAs (miRNAs or miRs) as important biomarkers in the diagnosis, prognosis, and treatment of CSCC. This study aims to investigate the effects of miR-203 on the behaviors of CSCC cells and possible mechanisms associated with protein regulator of cytokinesis-1 (PRC1) and Wnt/β-catenin signaling pathway. PRC1 was suggested as a target of miR-203 in squamous cell carcinoma cell line 1 (SCL-1) cells by dual-luciferase reporter gene assay. Based on the immunohistochemical staining and qRT-PCR, PRC1 was abundantly expressed while miR-203 was poorly expressed in CSCC tissues. miR-203 mimic or inhibitor was transfected into SCL-1 cells to upregulate or downregulate its expression. Upregulation of miR-203 downregulated PRC1 expression to block the Wnt/β-catenin signaling pathway. By conducting 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), scratch test, and Transwell and flow cytometric analyses, miR-203 was witnessed to restrain SCL-1 cell proliferation, migration, and invasion while accelerating their apoptosis. The rescue experiments addressed that inhibition of the Wnt/β-catenin signaling pathway conferred the anti-tumor effect of miR-203. These results establish a tumor-suppressive role for miR-203 in CSCC cell line SCL-1. Hence, miR-203 has promising potential as a therapeutic target for CSCC.